Characteristics of dental note taking: a material based themed analysis of Swedish dental students - Lindberg, Viveca (BMC Med Educ, 2020)
BACKGROUND: The transition from upper secondary to higher education and from higher education to professional practice requires that students adapt to new literacy practices, academic and professional. However, there is a gap of knowledge regarding literacy practices in dental education. Therefore, the aim of this study was to identify what characterizes dental students’ notetaking and secondarily to determine what dental students express regarding their notetaking. METHODS: To analyze students’ perspectives about the purposes of notetaking and to examine their written notes in depth, three volunteer students, out of the 24 students that voluntarily and anonymously handed in their notes, were interviewed. The three undergraduate dental students that participated in this material-based, semi-structured interview study, framed within a New Literacy Studies approach, were on their third year (6th semester). The focus of these material-based interviews was on each student’s notes. Questions prepared for semi-structured interviews were open-ended and allowed for individual follow-up questions related to the interviewee’s answer. To analyze the outcome of the interviews a thematic analysis was used. RESULTS: From the material-based interviews eight themes that relate to what, how and for what purpose students write were discerned. These eight themes include professional vocabulary, core content as well as clinical examples that belong to what students read and write; multimodal accentuation as well as synthesis that belong to how students read and write; and mnemonic strategies, academic purposes, and professional purposes that belong to for what purpose students read and write. CONCLUSIONS: Findings from the interviews indicate that the digital development, offering a variety of available tools, has expanded the notion of notetaking. This study identified that dental students’ notetaking has changed during their education from initially being synchronous, to also include multimodal and asynchronous writing, making notetaking more of a writing practice. Further, students’ writing practices seem to be motivated by their knowledge formation in relation to a subject matter, but also in relation to their experiences during clinical training. Although, our hypothesis was that the main purpose of notetaking and writing was to pass their course examinations, this study showed that students that were half-way through their dental education, are aware that literacy practices are for learning for their future profession, and not only for passing their exams.